2011
DOI: 10.5301/jva.5000001
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Ulcerated, Bleeding Autologous Dialysis Fistulas

Abstract: The ulcerated autologous dialysis fistula is a life-threatening lesion and requires prompt surgical intervention to reduce mortality. The frequency of this problem appears to be increasing. Simple suturing of the ulcers was not consistently effective in remedying the problem and should be utilized as a temporizing measure until surgical correction can be undertaken. Fistulas can be uniformly salvaged with surgical intervention enabling uninterrupted dialysis treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
0
21
1
Order By: Relevance
“…Moreover, a regional investigation conducted by Ellingson et al 3 suggested that these national figures were potentially underestimated owing to major under-reporting of fatal haemorrhages. Finally, of 24 patients with ulcerated lesions retrospectively identified by Jaffers and Fasola, 4 two patients died from a major haemorrhagic event before surgical consultation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, a regional investigation conducted by Ellingson et al 3 suggested that these national figures were potentially underestimated owing to major under-reporting of fatal haemorrhages. Finally, of 24 patients with ulcerated lesions retrospectively identified by Jaffers and Fasola, 4 two patients died from a major haemorrhagic event before surgical consultation.…”
Section: Discussionmentioning
confidence: 99%
“…If the necrosis area is limited, minimal skin mobilisation and suturing or advancement flap have been reported to be successful after ulcer excision and vessel wall suturing. 4 For larger ulcerated areas, a locally rotated fullthickness skin flap might be the best option. In 1946, Limberg described a standardised locally rotated flap with 60 and 120 angles for primary closure of rhomboid defects after excision of skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate-sized balloon catheter is selected by perioperative ultrasound measurements and proximal and/or distal vascular control are achieved by endo-occlusion (Figure 4 The topic of SN overlying an AVF cannulation site has been generally reviewed with reports focusing on vascular access aneurysms and bleeding. [1][2][3][4][5][6] Area (or cluster) cannulation is frequently implicated as a major factor in formation of these lesions and should be avoided. 7 Other related factors may include elevated AVF pressure due to high flow or outflow vein stenosis and are commonly associated with these lesions.…”
Section: Technical Notementioning
confidence: 99%
“…Skin necrosis (SN) overlying an arteriovenous fistula (AVF) at a site of repetitive cannulation ( Figure 1) is a relatively common and potentially life-threatening situation that may complicate an AVF. [1][2][3][4][5][6] It presents an urgent dilemma for the vascular access surgeon with the risk of exsanguination in addition to a desire for maintaining a functional AVF after repair. Limited AVF length is a common problem and may render cannulation sites unusable when surgical proximal and/or distal control are established.…”
Section: Introductionmentioning
confidence: 99%